Utilization of FABA (Fly Ash-Bottom Ash) as a Planting Medium and Goat Manure with Cow Rumen Bioactivator on the Growth and Yield of Shallots (Allium ascalonicum L). : Pemanfaatan Faba (Fly Ash-Buttom Ash) sebagai Media Tanam dan Dosis Kotoran Kambing Dengan Bioaktivator Rumen Sapi Terhadap Pertumbuhan dan Hasil Bawang Merah (Allium Ascalonicum L.) - Agustina, Rega; Podesta, Fiana; Fitriani, Dwi; Harini, Ririn; Suryadi (Universitas Muhammadiyah Sidoarjo, 2024)
Shallots (Allium ascalonicum L.) is a leading horticultural commodity in North Sumatra. This study aims to analyze the interaction between Fly Ash and Bottom Ash (FABA) and goat manure with cow rumen bioactivator on the growth and yield of shallots, evaluate the effect of FABA as a planting medium, and examine the effect of goat manure with cow rumen bioactivator on the growth and yield of shallots. The study was conducted at Jl. Raya Darma Wanita, Bentiring Permai Village, Bengkulu City, in September–November 2023. The method used was a Completely Randomized Design (CRD) with two factors: FABA dose (F0: without FABA, F1: 20%, F2: 30%, F3: 40%, F4: 50%) and goat manure dose (K0: without fertilizer, K1: 5 tons/ha, K2: 10 tons/ha, K3: 15 tons/ha). There were 20 treatment combinations repeated three times with 180 plants. The results showed that the interaction between FABA and goat manure did not significantly affect all parameters. FABA significantly increased plant height at the ages of 14, 28, 42, and 56 HST, as well as plant fresh weight, plant dry weight, bulb fresh weight, and bulb dry weight. In contrast, goat manure did not significantly affect all parameters. This study concluded that FABA effectively increases the growth and yield of shallots, while goat manure requires further research for optimal results.